Put Your Imperfections Behind You: Temporal Landmarks Spur Goal Initiation When They Signal New Beginnings. (December 2015) - Dai, Hengchen; Milkman, Katherine L.; Riis, Jason
People often fail to muster the motivation needed to initiate goal pursuit. Across five laboratory experiments, we explored occasions when people naturally experience enhanced motivation to take actions that facilitate goal pursuit and why certain dates are more likely to spur goal initiation than others. We present causal evidence that emphasizing a temporal landmark denoting the beginning of a new time period increases people's intentions to initiate goal pursuit. In addition, we propose and show that people's strengthened motivation to begin pursuing their aspirations following such temporal landmarks originates in part from the psychological disassociation these landmarks induce from a person's past, imperfect self.